ANALYSIS OF THE ECONOMIC EFFICIENCY AND SOCIAL IMPACT OF ECOLOGICAL MARKETING STRATEGIES IN THE FIELD OF CLEANING PRODUCTS (American Journal of Business Management, Economics and Banking, 2025)
This study explores the economic effectiveness and social impact of ecological marketing strategies in the hygiene products sector. The analysis reveals that green approaches help reduce costs, enhance consumer trust, and strengthen brand loyalty. Eco-labeling, sustainable packaging, innovation, and transparent communication emerged as the most effective strategies. The findings confirm that ecological marketing can serve as a practical and impactful management tool.